Regional payment agreements: An alternative to currency convertibility? - Bruchanski, Marcelo Daniel (2023)
Regional Payment Agreements (RPAs) replicate, on a regional scale, John M. Keynes’s proposal at the Bretton Woods Conference, based on the recording and subsequent clearing of transactions. The analysis of the three “founding” RPAs from the Golden Age (Finland-USSR, European Payments Union and the LAFTA-LAIA Agreement on Reciprocal Payments and Credits) suggests that, in general, these agreements fulfiled their objectives: saving foreign currency and promoting trade. Hence, RPAs would present an alternative to currency convertibility for current account transactions.